2020
DOI: 10.1186/s42483-020-00048-9
|View full text |Cite
|
Sign up to set email alerts
|

Silicon modulates multi-layered defense against powdery mildew in Arabidopsis

Abstract: Silicon (Si) has been widely employed in agriculture to enhance resistance against pathogens in many crop plants. However, the underlying molecular mechanisms of Si-mediated resistance remain elusive. In this study, the Arabidopsispowdery mildew pathosystem was employed to investigate possible defense mechanisms of Si-mediated resistance. Because Arabidopsis lacks efficient Si transporters and thus is a low Si-accumulator, two heterologous Si influx transporters (from barley and muskmelon) were individually ex… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 51 publications
2
9
0
Order By: Relevance
“…For example, silicification is a potent physical defence against leaf‐chewing herbivores, particularly due to its abrasive nature (Andama et al., 2020; Massey & Hartley, 2009). Moreover, silicification could potentially affect phytohormonal pathways, such as jasmonic acid (JA) following herbivory (Hall et al., 2019) and salicylic acid (SA) upon pathogen infections (Wang et al., 2020). Silicification could also affect plant performance (Schaller et al., 2017) and other plant functional traits, such as cell/tissue structures, growth, physiology and elemental composition (Cooke & Leishman, 2011b; Detmann et al., 2012; He et al., 2015; Klotzbücher et al., 2018).…”
Section: Introductionmentioning
confidence: 99%
“…For example, silicification is a potent physical defence against leaf‐chewing herbivores, particularly due to its abrasive nature (Andama et al., 2020; Massey & Hartley, 2009). Moreover, silicification could potentially affect phytohormonal pathways, such as jasmonic acid (JA) following herbivory (Hall et al., 2019) and salicylic acid (SA) upon pathogen infections (Wang et al., 2020). Silicification could also affect plant performance (Schaller et al., 2017) and other plant functional traits, such as cell/tissue structures, growth, physiology and elemental composition (Cooke & Leishman, 2011b; Detmann et al., 2012; He et al., 2015; Klotzbücher et al., 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Pathogen induced deposition of callose may help seal off nutrients, water and impair signalling between pathogen and host 23 . Furthermore, based on work on Arabidopsis thaliana , it was suggested 33 and later corroborated 34 that callose formation was important for Si accumulation, forming a framework for Si deposition to strengthen the cell wall. The elevated expression of GLS5 near pathogen infection attempts in the current experiments appear to support this hypothesis.…”
Section: Discussionmentioning
confidence: 92%
“…This is consistent with recent findings in Arabidopsis . Wang et al (2020) found that Si-treatment will enhance the accumulation of JA and the resistance to powdery mildew. However, Si fertilization still enhances powdery mildew in the Arabidopsis coi1 mutant ( Wang et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“… Wang et al (2020) found that Si-treatment will enhance the accumulation of JA and the resistance to powdery mildew. However, Si fertilization still enhances powdery mildew in the Arabidopsis coi1 mutant ( Wang et al, 2020 ). Overall, we conclude that JA biosynthesis, but not JA signaling pathway, is required to induce Si-mediated LB resistance.…”
Section: Discussionmentioning
confidence: 99%